2018
DOI: 10.1088/1361-665x/aac28a
|View full text |Cite
|
Sign up to set email alerts
|

A shape memory polymer concrete crack closure system activated by electrical current

Abstract: The presence of cracks has a negative impact on the durability of concrete by providing paths for corrosive materials to the embedded steel reinforcement. Cracks in concrete can be closed using shape memory polymers (SMP) which produce a compressive stress across the crack faces. This stress has been previously found to enhance the load recovery associated with autogenous self-healing. This paper details the experiments undertaken to incorporate SMP tendons containing polyethylene terephthalate (PET) filaments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…[16][17][18] In essence, shape recovery of electroactive SMP is stimulated by the heat generated from electricity. [19] When certain voltage is applied to electroactive SMP, the electrical energy is converted into thermal energy due to Joule heating effect and makes the temperature exceeding its shape transition temperature to activate shape recovery. [20] Accordingly, electroactive is more apt to be fulfilled in SMPs with low shape transition temperatures.…”
Section: Doi: 101002/macp201900164mentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] In essence, shape recovery of electroactive SMP is stimulated by the heat generated from electricity. [19] When certain voltage is applied to electroactive SMP, the electrical energy is converted into thermal energy due to Joule heating effect and makes the temperature exceeding its shape transition temperature to activate shape recovery. [20] Accordingly, electroactive is more apt to be fulfilled in SMPs with low shape transition temperatures.…”
Section: Doi: 101002/macp201900164mentioning
confidence: 99%
“…Electroactive SMPs have been explored extensively since electricity is a very convenient stimulus for SMPs, especially in applications where direct heat is inconvenient or difficult to be executed . In essence, shape recovery of electroactive SMP is stimulated by the heat generated from electricity . When certain voltage is applied to electroactive SMP, the electrical energy is converted into thermal energy due to Joule heating effect and makes the temperature exceeding its shape transition temperature to activate shape recovery .…”
Section: Introductionmentioning
confidence: 99%
“…The surface of each panel was painted with white then black emulsion paint to create a speckled pattern that could be picked FIGURE 5 | Shape memory PET tendon crack closure system (Teall et al, 2018).…”
Section: Monitoring Equipmentmentioning
confidence: 99%
“…This followed on from previous research at the university into the use of polyethylene terephthalate (PET) strips to induce a compressive stress in concrete, which reduces the crack size and enhances autogenous healing (Jefferson et al, 2010;Dunn et al, 2011;Isaacs et al, 2013;Hazelwood et al, 2015;Teall et al, 2015). Working with Bradford University, high-shrinkage PET tendons were developed for these site trials (Teall, 2016;Teall et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the resistance of the concrete with complex graphite and steel slag increased with the increase of strain under uniaxial compression, and the process showed concordant monotonicity [1,2]. A shape memory polymer concrete crack closure system activated by electrical current was investigated by Teallet et al [3]. This stress was previously found to enhance the load recovery associated with autogenous self-healing.…”
Section: Introductionmentioning
confidence: 99%